1997
DOI: 10.1021/ja953439d
|View full text |Cite
|
Sign up to set email alerts
|

The Temperature-Dependence of Hydrophobic Association in Water. Pair versus Bulk Hydrophobic Interactions

Abstract: The temperature dependence of hydrophobic interactions of methane-like particles in water is analyzed in terms of free energy, entropy, internal energy, and the second osmotic virial coefficient. A large computational effort (approximately 15 ns cumulative trajectory length at each temperature) has been undertaken in order to guarantee reliable free energy and entropy data. At 300 K association is controlled by entropy, but as the temperature rises the internal energy takes over and dominates at 500 K. Both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
115
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(133 citation statements)
references
References 43 publications
18
115
0
Order By: Relevance
“…All models show an increase of the first peak with rising temperature. This observation is well in accordance with the interpretation that the association of two hydrophobic particles is stabilised by minimising the solvation entropy penalty and has already been reported by a large number of publications [8,9,14,16,20,21,23,24,25,27]. The idea is schematically depicted in Figure 7: The enhanced ordering of the solvent molecules in the hydration shell results in a negative solvation entropy.…”
Section: Hydrophobic Interactionsupporting
confidence: 91%
See 1 more Smart Citation
“…All models show an increase of the first peak with rising temperature. This observation is well in accordance with the interpretation that the association of two hydrophobic particles is stabilised by minimising the solvation entropy penalty and has already been reported by a large number of publications [8,9,14,16,20,21,23,24,25,27]. The idea is schematically depicted in Figure 7: The enhanced ordering of the solvent molecules in the hydration shell results in a negative solvation entropy.…”
Section: Hydrophobic Interactionsupporting
confidence: 91%
“…As a consequence, with increasing temperature the association of hydrophobic particles is found to be enhanced in order to minimise the solvation entropy penalty [8,9]. This entropy-driven association process is usually referred to as hydrophobic interaction and has been subject of numerous simulation studies [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. * dietmar.paschek@udo.edu; http://ganter.chemie.uni-dortmund.de/~pas/ Hydrophobic effects are considered to play an important role concerning protein stability and other self assembly phenomena [4,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…It has been established long ago that PMF between two solute particles exhibits two distinct minima corresponding to contact (CC) and solvent-separated configuration (SSC). [2][3][4] The effect of temperature, 5,6 pressure, [7][8][9] solute concentration, 10 solvent polarization, 11 and solventsolvent interactions 12 on the structure of PMF has been reported. A lot can be learned from PMFs accompanying functions, namely, enthalpy, entropy, and heat capacity change for bringing two solutes from infinity to a certain distance.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they are seen as an important driving force with regard to the folding of proteins [4,5,6]. Consequently, a wealth of studies of hydrophobic interactions using molecular simulation techniques have been undertaken over the past three decades [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. Simulation studies have revealed that the contact state of a pair of hydrophobic particles in aqueous solution is entropically stabilized at ambient conditions [10,11].…”
Section: Introductionmentioning
confidence: 99%